Bulk Density of Shrub Types and Tree Crowns to Use with Forest Inventories in the Iberian Peninsula - Nunes, Leónia (2022)
This research was also funded by the National Institute of Agricultural Research of Spain (INIA) through project RTA2017-00042-C05-02, co-funded by FEDER. Publisher Copyright: © 2022 by the authors. Licensee MDPI, Basel, Switzerland.